MANGROVE HEALTH INDEX IN SEGARAJAYA VILLAGE, TARUMAJAYA DISTRICT, BEKASI REGENCY, WEST JAVA - Wardono, Suko; Romauli S, Angelina Yohana; Rizkiah, Riza; Rosalina, Dwi (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Mangrove forests thrive under tidal influences and play vital ecological, physical, and economic roles. However, without proper management, they are prone to degradation. In Segarajaya Village, Tarumajaya District, Bekasi Regency, West Java, mangroves face threats from human activities such as land clearing for aquaculture and pollution from plastic and domestic waste. This study, conducted from February 25 to April 20, 2025, used the Mangrove Health Index (MHI) method by assessing canopy cover, density, stem diameter, and environmental factors (salinity, water and air temperature, soil pH, and substrate). The aim was to evaluate mangrove health based on these parameters. Three observation stations were established: Station 1 (Rhizophora apiculata, Avicennia marina, Sonneratia caseolaris), Station 2 (Bruguiera gymnorhiza, Sonneratia caseolaris), and Station 3 (Avicennia marina). The MHI results indicated a moderate health status with an average value of 61.78% (Station 1: 62.69%, Station 2: 61.63%, Station 3: 61.02%). Environmental conditions averaged 30.44‰ salinity, 27.94°C water temperature, 30.89°C air temperature, soil pH 7.33, and sandy clay to muddy substrates. The study provides baseline data for mangrove management and conservation efforts.